2020
DOI: 10.1111/apt.15739
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative accuracy of ferritin, transferrin saturation and soluble transferrin receptor for the diagnosis of iron deficiency in inflammatory bowel disease

Abstract: Background:The diagnosis of iron deficiency is based on ferritin and transferrin saturation (TfS) in inflammatory bowel disease (IBD) patients, yet guideline thresholds are not evidence-based. Soluble transferrin receptor (sTfR) is one of the best noninvasive tests in patients with inflammation. Aims:To evaluate the accuracy of ferritin and/or TfS for diagnosing iron deficiency in IBD and identify the optimal thresholds of these parameters using sTfR as reference. Methods: Two hundred and two patients (2072 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…The level of transferrin saturation, however, can serve as a valuable tool for identifying iron overload. Transferrin's iron-binding sites are estimated to be a proportion of its total number of iron-binding sites ( Daude et al, 2020 Jun ). Ferritin levels higher than 300 µgL -1 are present in about 20% of caucasian men irrespective of age.…”
Section: Hyperferritinemiamentioning
confidence: 99%
“…The level of transferrin saturation, however, can serve as a valuable tool for identifying iron overload. Transferrin's iron-binding sites are estimated to be a proportion of its total number of iron-binding sites ( Daude et al, 2020 Jun ). Ferritin levels higher than 300 µgL -1 are present in about 20% of caucasian men irrespective of age.…”
Section: Hyperferritinemiamentioning
confidence: 99%
“…Regarding the sTfR, considered one of the best indicators of iron deficiency anemia (21,25) , especially the sTfR-SF (25) , it is interesting to note that there was higher concentration in both conventional and infliximab groups compared to remission and control group, at baseline, 2 and 6 months after treatment. One study with children (25) showed that sTfR and sTfR/log ferritin were significantly higher in the IBD group than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess anemia in IBD, the most useful body iron status indicators are transferrin saturation (8)(9)(10) , soluble transferrin receptor (sTfR) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) , serum iron (11,12,17,(22)(23)(24) , soluble transferrin receptor/ ferritin ratio (sTfR-SF) (12,14,16,17,25) and transferrin (17,26,27) ; while erythrocyte sedimentation rate (ESR) (11,17,22,23,26,28) , interleukin-6 (IL-6) (22,24,26) , ferritin (11,12,16,17,(23)(24)(25)(26)(27)(28)(29)(30) , albumin (24) an...…”
Section: Introductionmentioning
confidence: 99%
“…Bei aktiver Entzündung und Ferritin-Werten zwischen 30-100 μg/l liegt häufig eine Kombination aus einer ACD und einem Eisenmangel vor [563]. Eine aktuelle französische Studie an 129 Crohn-Patient*innen zeigte, dass sich weder für Ferritin noch für die Transferrinsättigung Grenzwerte finden lassen, die mit hinreichender Genauigkeit die Feststellung einer Eisenmangelanämie erlauben [566]. Insofern sollte zur Feststellung eines Eisenmangels das Verhältnis von löslichem Transferrin-Rezeptor (sTR) und Serum-Ferritin bestimmt werden (sTR/log Ferritin-Index) [563,567,568].…”
Section: Anämieunclassified